1988
DOI: 10.1016/0735-1097(88)90402-0
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated coronary vascular disease in the heart transplant patient: Coronary arteriographic findings

Abstract: Annual coronary arteriograms have been obtained from all heart transplant recipients at Stanford University Medical Center since 1969. Angiographic lesions in 81 transplant patients exhibiting coronary vascular disease were classified into three categories: type A, discrete or tubular stenoses; type B, diffuse concentric narrowing; and type C, narrowed irregular vessels with occluded branches. The 81 arteriograms showing transplant coronary vascular disease were contrasted with 32 from nontransplant patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
180
0
11

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 465 publications
(195 citation statements)
references
References 9 publications
4
180
0
11
Order By: Relevance
“…1,2 This posttransplant arteriopathy is characterized by rapid development, 3,4 concentric narrowing of smaller coronary arteries, 5,6 and the lack of correlation with known atherogenic risk factors. [1][2][3][4][5][6] Understanding the etiology of accelerated atherosclerosis might allow identification of patients at risk for this complication.It has been suggested that ischemic injury of the heart during the peritransplant period significantly contributes to the development of accelerated atherosclerosis in heart transplant patients. 7 A correlation between LDL oxidation and atherogenesis was first suggested by experiments showing that oxidized LDL mediated injury to endothelial cells (reviewed in Reference 8) and was further supported by studies showing a protective effect of antioxidants against progression of atherosclerosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 This posttransplant arteriopathy is characterized by rapid development, 3,4 concentric narrowing of smaller coronary arteries, 5,6 and the lack of correlation with known atherogenic risk factors. [1][2][3][4][5][6] Understanding the etiology of accelerated atherosclerosis might allow identification of patients at risk for this complication.It has been suggested that ischemic injury of the heart during the peritransplant period significantly contributes to the development of accelerated atherosclerosis in heart transplant patients. 7 A correlation between LDL oxidation and atherogenesis was first suggested by experiments showing that oxidized LDL mediated injury to endothelial cells (reviewed in Reference 8) and was further supported by studies showing a protective effect of antioxidants against progression of atherosclerosis.…”
mentioning
confidence: 99%
“…1,2 This posttransplant arteriopathy is characterized by rapid development, 3,4 concentric narrowing of smaller coronary arteries, 5,6 and the lack of correlation with known atherogenic risk factors. [1][2][3][4][5][6] Understanding the etiology of accelerated atherosclerosis might allow identification of patients at risk for this complication.…”
mentioning
confidence: 99%
“…[1][2][3] The angiographic characteristic of allograft vasculopathy is defined as diffuse concentric narrowing in the epicardial medium and small arteries. 12 The only definite therapy for such diffuse disease is repeat transplantation, but the survival rate of retransplantation is worse than for initial transplantation and is limited by organ availability. 13 Coronary artery bypass surgery also is of limited value in the diffuse, small-vessel disease manifested in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…3,15,16 Serial angiographic studies in heart transplantation recipients have demonstrated an increased prevalence of coronary abnormalities associated with longer graft survival. 6 By 5 years after transplantation, 40% to 50% of patients have angiographic evidence of disease. 6,17…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Annual coronary angiography, which can detect severe transplantation coronary artery disease (TCAD) as early as 1 to 2 years after heart transplantation, has been used for diagnostic and surveillance purposes because patients may remain asymptomatic until myocardial infarction, congestive heart failure, cardiac arrhythmia, or sudden death develop. 3,7 Angiography is relatively insensitive for detecting early or less severe TCAD because of its diffuse nature and because the early phases of intimal hyperplasia may be associated with vessel wall expansion (positive remodeling) and minimal luminal narrowing.…”
mentioning
confidence: 99%